How does information technology enhance the agricultural resilience: the practice of digital inclusive finance in China - Wan, Yanglu; Lu, Wei; Wang, Rui; Zhan, Mingfang; Wang, Yong (Frontiers in Sustainable Food Systems, 2025)
IntroductionEnhancing industrial resilience is the key to achieving sustainable growth in the agricultural economy. The rapid development of information technology nowadays provides innovative solutions for stabilizing agricultural production and supply chains.MethodsBased on panel data from 270 Chinese cities from 2012 to 2023, this study employed a series of econometric methods, such as two-way fixed effects, two-stage least squares, threshold models, and spatial Durbin models, to analyze the impact of information technology advancements represented by digital inclusive finance (DIF) on the agricultural economy.ResultsThe results of data analysis show that DIF has significantly enhanced the agricultural resilience (AR). This positive effect still holds true after robustness tests and the elimination of endogeneity issues. However, this promoting effect is not linear but shows a threshold effect that first declines and then rises. In other words, there is a clear U-shaped relationship in the impact of DIF on the AR. The results of the heterogeneity analysis show that it can present a significant positive effect in different regions, but the effect is more intense in the eastern region. The results of the spatial Durbin model show that this positive effect has a spatial spillover effect. DIF will also have a technological spillover effect on neighboring regions through information platforms, economic exchanges, and trade transportation channels. The results of the mechanism analysis show that entrepreneurial activity is a very important mediating variable.DiscussionThis study takes China's DIF practice as a specific analytical perspective, revealing the positive role of information technology progress on the agricultural economy. Our findings contribute to the achievement of United Nations Sustainable Development Goals 1 and 2.